PRE-RAMADAN COUNSELLING IN ADULTS WITH TYPE 2 DIABETES (T2D) IN INSTITUT ENDOKRIN HOSPITAL PUTRAJAYA - Siau, Yong Shern; Marzukie, Marisa Masera; Azwan, Raja Nurazni Raja; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Pre-Ramadan counselling is essential for safe fasting in Muslims with Type 2 Diabetes (T2D). Structured education on risk stratification, glycaemic monitoring, and medication adjustments reduces hypoglycaemia, hyperglycaemia, and dehydration risks. We audited outcomes before and after implementing pre-Ramadan continuous medical education (CME) for clinicians at Institut Endokrin Hospital Putrajaya (IEHPJ) to assess its impact on patient counselling. METHODOLOGY We conducted a retrospective study to audit pre-Ramadan counselling practices before (December 2024) and after (February 2025) CME implementation at IEHPJ using universal sampling from electronic medical records. We retrieved and reviewed records of all Muslim patients attending T2D clinics during the study period. RESULT This study included 693 patients, 309 from the pre-CME period and 384 in the post-CME period. There were 48.3% male patients with a mean age of 57.5 years (±12). Diabetes duration was >10 years at 62.5%. The mean HbA1c of our patients was 8.4% (±2.0). The majority of patients (91.6%) had eGFR >30 mL/min/1.73m². Regarding medications, 20.3% were on non-sulphonylurea oral glucose-lowering drugs with or without GLP-1-RA, while the remaining were on insulin and/or sulphonylurea. 16.1% were on a basal insulin regime, and 48.9% were on more complex multiple daily injection regimes. Pre-Ramadan counselling significantly increased from 33.9% (105/309) pre-CME to 58.4% (230/394) post-CME (p <0.001). Even though most patients were on treatment regimens that predisposed them to hypoglycaemia during fasting, IDF-DAR risk scoring assessment remained low in both groups. Although IDF-DAR risk scoring improved from 13 to 42 patients after the CME, this was not statistically significant. CONCLUSION CME improved counselling rates in our clinics, but gaps in risk assessment persist. Implementing structured protocols in the future could further reduce risks during Ramadan fasting.